Development of Community–Based Tourism Products of Ban Thong Kung, Kamphaeng Phet Province - Chitkati, Praphol; Meepripruk, Montha; Funkhiaw, Adirek; Buadee, Nattaphanee; Ussasarn, Kanika; Anurakwattana, Orathai; Sirikitsathien, Chayanan; Khaokham, Pimprapai; Jakae, Okama; Tonboon, Nantanat (Area Based Development Research Journal, 2021)
The large-scale farming community of ladyfinger banana is located in Ban Thong Kung, Tha Phutsa subdistrict, Klong Klung district, Kamphaeng Phet province. It is known as a traditional community of the province. The unique way of life and culture is suitable for developing community–based tourism products. The research first aims to creatively develop community–based tourism products in relation to local history, culture, and identity. Thus, the development are conducted in three aspects, namely the local sweet herb crunchy cereal bar, local cuisine based on local banana farmer’s recipes, and the travel route of tourist attractions. The second objective is to develop community potential based on Thailand Community-Based Tourism (CBT) Standard. The third objective is to develop marketing channels for the community-based tourism. After discovering problems and investigating the potential of the community in terms of tourism, an assessment of the community potential based on CBT Thailand criteria. The development process was conducted as follows: 1) planning and developing with the cooperation between researchers and the community, 2) developing local products, 3) developing community potential, and 4) developing marketing channels. The development resulted in increasing community income to 80,000 bath/year and increasing the number of visitors to 660 visitors/year. The highest score of evaluating tourism potential based on CBT Standard was the aspect of preserving and promoting cultural heritage. Finally, the project yields the development of marketing channels both online and offline including websites, social media, in-store selling, joining trade shows and exhibitions, and selling to local retail stores.